Investigation of three level code division multiplexing performance over high speed optical fiber communication system - Khosravi, Faranak; Mokhtar, Makhfudzah; Abas, Ahmad Fauzi; Mahdi, Mohd Adzir; Mahdiraji, Ghafour Amouzad (IEEE, 2013)
In this research, performance of Three Level Code Division Multiplexing (3LCDM) technique is investigated for high-speed optical fiber communication systems. It is shown that 40 Gb/s (2×20 Gb/s) 3LCDM system perform s better than the conventional 40 Gb/s non return to zero (NRZ-OOK) in term the dispersion tolerance. At 40 Gb/s, the lower level displays a nearly analogous behaviour of positive and negative chromatic dispersions tolerance which stands about ±98 ps/nm while the upper level has chromatic dispersion tolerance of ±81 ps/nm at BER of 10-9. These values are higher than that of 40 Gb/s conventional NRZ, which is approximately ±49 ps/nm.